The Influence Of Technology Acceptance, Effectiveness, Motivation, Opportunity And Social Identity Towards Customer Know-How Dota Gamers - Nugrahani, Rah Utami (2021)
Focusing on Indonesian active online Dota2 gaming players, this study investigates the antecedents of customer-to-customer online knowhow exchange (C2COKHE) and moderating effect of social identity (SI) on this behavior. C2COKHE is important because interactions between gamers carried out in the community to discuss strategies, sharing of experiences and knowledge related to Dota2 games will help gamers to win the competitions involved in it.